Quality Management of Students in Islamic Boarding Schools - Ibnu Chudzaifah; Afroh Nailil Hikmah; Anik Ambarwati (Journal of Quality Assurance in Islamic Education (JQAIE), 2022)
Islamic boarding school is one of the Islamic educational institutions which, along with the progress of science and technology, develops to streamline the broadcasting business and practice the teachings of Islam. In the process of implementation, Islamic boarding schools carry out a process of fostering knowledge, attitudes, and skills related to religious aspects. The main objective is to strive for the formation of virtuous individuals (akhlaq al-karimah) with consistent religious practices (istiqamah). This study aims to describe: (1) the pattern of character building for students at the Roudlotul Khuffadz Islamic Boarding School, and (2) the supporting and inhibiting factors in character building for students at the Roudlotul Khuffadz Islamic Boarding School. This research uses a qualitative research type with a descriptive approach. Data were collected by using observation, interview, documentation, and literature review techniques that are relevant to the research conducted. The methods used in data analysis are data reduction, data presentation, and concluding. The results of this study indicate that the pattern of character building for students at the Roudlotul Khuffadz Islamic Boarding School is carried out through material development, religious development, honesty development, discipline development, independence development, responsibility development, skills development, and leadership development.